The land is a map : placenames of indigenous origin in Australia - Hercus, L. A. (Luise Anna), 1926-2018; Hodges, Flavia; Simpson, Jane Helen (ANU E Press, 2009)
"The entire Australian continent was once covered with networks of Indigenous placenames. These names often evoke important information about features of the environment and their place in Indigenous systems of knowledge. On the other hand, placenames assigned by European settlers and officials are largely arbitrary, except for occasional descriptive labels such as 'river, lake, mountain'. They typically commemorate people, or unrelated places in the Northern hemisphere."--Cover